Relative Impact of Bank Credit on Manufacturing Sector in Nigeria - Ilemona, Adofu Ilemona; Anjola Wilson, Daniel (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The study examined the relative impact of bank credit on manufacturing sector in Nigeria from 1981 to 2018. The techniques adopted in the study include; ordinary least square (OLS) method, Augmented Dickey Fuller (ADF) unit root test, Johansen cointegration test and error correction mechanism (ECM) technique. The data used for the analysis is secondary source of data and the model adopted in the work is a linear regression model. The findings showed that lending rate, credit to private sectors, and loans and advances to manufacturing sector contributed positively to the manufacturing sector output with the exception of inflation rate. Therefore, the study recommends that government should, through the Central Bank of Nigeria, pursue policies that lower interest rate (cost of capital) and reduce inflation on one hand and increase money supply as well as loans and advances to the investors in order to increase the output of the manufacturing sector which is capable of stimulating economic growth.